Real-world evaluation of teclistamab for the treatment of relapsed/refractory multiple myeloma (RRMM): an International Myeloma Working Group Study - Carlyn Rose Tan; Sireesha Asoori; Chiung-Yu Huang; Larissa Brunaldi; Rakesh Popat; Efstathios Kastritis; Joaquin Martinez-Lopez; Radhika Bansal; Andre De Menezes Silva Corraes; Saurabh Chhabra; Ricardo Parrondo; Sikander Ailawadhi; et al. (Blood Cancer Journal)
Abstract Teclistamab, a BCMAxCD3-directed bispecific antibody, has shown high response rates and durable remissions in triple-class-exposed patients with relapsed/refractory multiple myeloma. We performed a retrospective study evaluating the efficacy and safety of teclistamab in 210 patients treated at 9 academic centers from five countries within the IMWG Immunotherapy Working Group Committee. Patients were heavily pretreated, with 83% having triple-class refractory disease and 44% with prior BCMA-targeted therapy. With a median follow-up of 5.3 months, the overall response rate (ORR) was 67% in 188 response-evaluable patients, including 55% with a very good partial response or better. The 6-month progression-free survival (PFS) and overall survival rates were 53% (95% CI, 46–61%) and 73% (67–80%), respectively. Patients who received prior BCMA-directed therapy compared to BCMA-treatment-naïve patients had a lower ORR (58.3 vs 74.0%; P = 0.03) and PFS (6-month PFS 43% [95% CI, 33–55%] vs 63% [54–73%]; logrank P = 0.004). Step-up dosing occurred in an outpatient setting for 23% of patients. CRS occurred in 54% of patients, and infections were reported in 56.2% of patients, with 22% having grade ≥3 infections. In this multicenter real-world study, we found that teclistamab can lead to rapid responses in heavily pretreated myeloma patients with comparable efficacy and safety profiles, as demonstrated in MajesTEC-1.